2003
DOI: 10.1504/ijtm.2003.003114
|View full text |Cite
|
Sign up to set email alerts
|

Negotiated agendas: families in science and technology museums

Abstract: Museum exhibition environment provides experiential learning through its messages to influence knowledge, attitudes and learning behaviours of visitors. Connections in visitors' cognitive, affective, emotional and physiological responses play a beneficial role in museum visits. The research focuses on how science centre as part of a museum discusses various practical methods to inspire visitor into having a response. The review features multiple theories of learning advocating how visitors learn and how these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 0 publications
1
34
0
3
Order By: Relevance
“…Among families in which caregivers had more formal education, group interactions focused on knowledge acquisition, concepts were “taught” or facilitated by a more knowledgeable individual (usually a parent), and learning unfolded unidirectionally. This resembled interactions documented in studies of families visiting museums (e.g., Briseño‐Garzón, Anderson, & Anderson, ; Moussouri, ) and the learning arrangements in schools.…”
Section: Evaluating Specific Projectssupporting
confidence: 57%
“…Among families in which caregivers had more formal education, group interactions focused on knowledge acquisition, concepts were “taught” or facilitated by a more knowledgeable individual (usually a parent), and learning unfolded unidirectionally. This resembled interactions documented in studies of families visiting museums (e.g., Briseño‐Garzón, Anderson, & Anderson, ; Moussouri, ) and the learning arrangements in schools.…”
Section: Evaluating Specific Projectssupporting
confidence: 57%
“…The social interactive function of museums has been valued by visitors and museum staff in Western cultural contexts (Falk and Storkdieck ; McManus ; Moussouri ). Museums as a public forum can trigger conversations among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding why visiting behavior and visiting outcomes differ from one visitor to another obliges us to look at questions that relate to visitors' personal identities and their sociocultural backgrounds. Numerous studies have concluded that visit motivation, as a predominant factor, plays a decisive role in influencing the museum visitation and learning outcomes (see Falk, Moussouri, and Colson ; Falk and Storksdieck ; Moussouri ; Packer and Ballantyne ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, a core ingredient of the visit experience is the family's own agenda about what the visit will hold, which incorporates prior knowledge and cultural itineraries. The visit experience itself is viewed as the result of the interaction between the family agenda on the one hand and the museum agenda on the other, constructed via a process of negotiation (Moussouri 2003(Moussouri , 2007. Discovering how this process unfolds during the visit and whether it is possible to identify relationships or indeed describe the underlying generating process in a principled manner is one of the main questions considered.…”
Section: London Zoo Case Studymentioning
confidence: 99%